A POLICY PERSPECTIVE ON COCONUT PROCESSING IN THE SOUTH PACIFIC ISLANDS - Dan M. Etherington (International Coconut Community Journal, 1988)
For many island nations of the South Pacific the coconut palm is the most important smallholder tree crop. Most attempts to introduce processing; beyond the copra stage have failed. At the same time there is a declining trend in copra prices. Unlike most other major coconut producing countries (Philippines, India, Indonesia, Sri Lanka, and Thailand), the South Pacific nations do not have significant expanding domestic urban markets. As a result they must look to alternative export markets and direct output to higher income, non‑traditional market niches. This paper, part of an on‑going research project, presents arguments in favour of an export ‘demand‑pull’ strategy for the coconut industry based on a re‑examination of the coconut as a total resource rather than only as a source of a raw vegetable oil. The effective use of this resource requires that the fruit be processed as a mature fresh nut and that all parts of the nut are used. The strategy implies a switch in research priorities, away from plant breeding and disease control towards processing, domestic and international shipping, energy policies and market development. Improved markets would in turn give renewed impetus to the continuation of the excellent plant breeding work that has already been done.